Character recognition "text to speech" - Almo, Niel M.; Comendador, Mary Grace S. (2007)
The computer world is constantly evolving each year. People make use of computers in many ways. Several applications known by man are implemented by introducing instructions to conventional computers. Until now, the target of computers to mimic the human brain and understand several tasks that humans don't know is still an on-going course of development.